Pemanfaatan Media Pembelajaran Digital dalam Meningkatkan Hasil Belajar dan Dampak Media Sosial Terhadap Perilaku Remaja Dalam Kehidupan Sehari-Hari - Azizah Azizah; Syamzaimar Syamzaimar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the use of digital learning media in improving learning outcomes and to examine the impact of social media on adolescents’ behavior in daily life in the digital era. The method used is a qualitative approach with a literature study (library research) design, conducted through the collection, review, and analysis of various relevant scholarly sources. The findings indicate that digital learning media play an important role in enhancing students’ motivation, engagement, and learning outcomes, as they are able to present material in an interactive, engaging, and easily understandable manner. On the other hand, social media has a dual impact on adolescents’ behavior. Its positive effects include ease of communication, access to information, and the development of creativity, while its negative effects include addiction, decreased learning focus, social comparison that lowers self-esteem, exposure to negative content, and the emergence of the Fear of Missing Out (FOMO) phenomenon, which can affect mental health.  Therefore, the wise use of digital media and proper supervision are necessary to support the improvement of educational quality while also fostering positive character development in adolescents.